DEVELOPMENTAL PATHS OF TEACHER PROFESSIONAL KNOWLEDGE IN MODELING-BASED TEACHING: ANALYSIS FROM A LONGITUDINAL SOCIO-HISTORICAL PERSPECTIVE - Oliveira, Leandro; Justi, Rosária (Investigações em Ensino de Ciências, 2024)
This study seeks to understand the development of teacher professional knowledge about models and modeling of a Chemistry Education associate professor, experienced and specialized in modeling-based teaching from a longitudinal socio-historical perspective. To do so, we analyzed her statements about her life history in terms of school and academic education, as well as professional practices for the last 18 years. Data were constructed from the transcription of those statements and interpreted according to theoretical-methodological procedures based on both a microgenetic analysis, promoting the decontextualization of contexts, and a macrogenetic analysis, from the recontextualization of contexts. This made it possible to trace her experiences from the student context at the secondary school to the experiences as university professor about to teach a course on models and modeling to a class of future teachers. The data analysis showed that, in her teaching history, various educational situations and contexts involving modeling-based teaching influenced her teacher professional knowledge about models and modeling, as well as how some turning points influenced and took part of the development of such knowledge. This study favors an understanding of the constitution of the subject (the associate professor) as it allows entering into her life contexts in which developmental paths of her teacher professional knowledge were identified and characterized. Furthermore, it contributes to the understanding of how science teachers can develop such knowledge from a longitudinal socio-historical perspective, which may have implications for teachers education.